The Impact of Classroom Environment on Student’s Willingness to Speak English - Thoriq Adiel Rofiif; Arif Suryo Priyatmojo (Journal of English Language and Education, 2026)
Many students feel reluctant to speak English in the classroom due to fear of making grammatical or pronunciation mistakes, negative evaluation from teachers or peers, and limited vocabulary to express their ideas effectively. This study aims to examine how the classroom environment influences junior high school students’ willingness to speak English by exploring the roles of teacher support, peer relationships, learning activities, and the physical classroom environment in shaping students’ confidence and classroom participation. This study employed a conceptual research design using a literature review approach. The review analyzed 32 peer-reviewed journal articles published between 2019 and 2025 that focused on classroom environment, willingness to communicate, speaking anxiety, and English language learning in EFL contexts. The literature was selected based on its relevance to the research objectives, publication quality, and empirical contribution to the topic. The findings reveal that a supportive classroom environment plays a crucial role in enhancing students’ willingness to speak English. Teacher support emerged as the most influential factor, followed by positive peer relationships, interactive learning activities, and a conducive physical classroom environment. Together, these factors reduce speaking anxiety, strengthen students’ confidence and motivation, and encourage more active participation in English-speaking activities, highlighting the importance of creating supportive learning environments to improve students’ communicative competence.